Pengaruh Perceived Value Terhadap Customer Satisfaction Di Pemandian Lubuk Lukum Kota Padang - Astuti Gita Riani; Nidia Wulansari (Lembaga Pengembangan Kinerja Dosen, 2024)
The research background is a complaints number from visitors and also the uniqueness and attractiveness of the Bathroom. The research purposes is to analyze the influence of perceived value on satisfaction of customer in the bathroom. This research type used is a quantitative method with an associative approach. The population of this study was 1,044 respondents. The research sample are 290 respondents. The way for collection of data is conducted through a questionnaire with a likert scale that has been done for validity and reliability. The research results shown that perceived value (X) had a positive impact on satisfaction of customer (Y) of 58.8%. The result of analysis linear regression obtained a counting F value of 18.724 with sig 0,000 < 0,05, this shown that the variable perceved value on client satisfaction was significantly influenced, and obtaining a count of t value of 20.283 with seg 0,000< 0,05..